Low birth weight infants outcome in a government general hospital of South India - Seepana, Somasekhara Rao; Sampathirao, Gunasekhar Raju (Indian Journal of Child Health, 2019)
Introduction: Globally, four million newborns die in the neonatal period. In India, 1.2 million neonatal deaths are reported every year. Low birth weight (LBW) is still a significant cause of neonatal deaths in India. Aim: The aim of the study was to determine the morbidity and mortality pattern of LBW neonates admitted in neonatal intensive care unit (NICU). Materials and Methods: A hospital based retrospective study was conducted at NICU of a government hospital of South India. Neonates admitted from April 2014 to March 2019 were included in the study and events from admission to discharge were recorded. Information was extracted retrospectively during admission from patient records and death certificates, using a pretested questionnaire. All neonates with incomplete and insufficient data were excluded from this study. The data collected were analyzed by frequency and percentages of various parameters of morbidity and mortality were calculated. Results: The data analysis showed that 7238 neonates were admitted to NICU during the study period. The majority of the neonates were males and the majority (4214, 58.22%) were born at full term of gestation, whereas preterm neonates born between 34 and 37 weeks were 1704 (23.54%) and